Strengthening coping strategies in relation to work-related stress: a systematization experience - Noguera Mena, Helder Gabriel (2020)
Objective: to analyze the transformations that occur in the client system in light of the systematized experiences, of the facilitator and the participants, in the mental health nursing intervention for the strengthening of coping strategies in the labor context of the company Hellman, Costa Rica. Method: The present work corresponds to a systematization of experiences of a nursing intervention in mental health, positioned from the model of Systems of Betty Neuman, for the strengthening of strategies of coping with stress. For the systematization of experiences, a mental health nursing intervention was articulated, using the nursing care process as the guiding thread, developed between April 27 and June 22, 2018. The analysis was carried out by means of a triangulation of data, where the experiences were analyzed from what is known about the different phenomena in the light of the theory Result: 14 people participated, 10 men and 4 women, with leadership roles. The outstanding individual learning was related to increased awareness for the identification of stressors and ADs directed to emotion and thought. Conclusion: Participants were able to identify work and daily stressors, as well as the ways in which they generate responses in the client system; in addition to recognition and training in coping strategies.